An analysis on chain characteristics of highstand geological disasters in high mountains and extremely high mountains based on optical remote sensing technology:A case study of representative large landslides in upper reach of Jinsha River - Wen LIU; Meng WANG; Sainan ZHU; Tianbin YU; Xichao HUANG; Ban SONG; Yu JIANG; Yujiang SUN (Zhongguo dizhi zaihai yu fangzhi xuebao, 2021)
The upper reaches of Jinsha River are typical high mountain canyon areas with strong terrain cutting and deep valleys. Affected by the Jinsha River fault zone, the slope integrity is poor and the rock mass is fragmented, which makes the mountain landslide prone to occur on both sides of the river. According to the hue, plane shape, deformation sign and microtopography of landslide hazards in remote sensing images, we establish the remote sensing interpretation signs. A total of 87 landslide were identified in Zhimenda-Shigu section of Jinsha River, including 40 large and 47 super-large ones. Based on the characteristics of regional geography and geological environment, we analyse the basic characteristics and spatial distribution of landslide. The landslide in the study area have obvious chain characteristics, including landslide –blocking river disaster chain, collapse – landslide – blocking river disaster chain, landslide – debris flow – blocking river disaster chain. Taking Sela landslide, Wangbuding landslide and Tange landslide as examples, the deformation characteristics and chain characteristics are analyzed in detail based on optical remote sensing technology. From the geographical view, the Jinshajiang fault zone obviously controls the plane distribution of the Zhimenda-Shigu section of the Jinsha River. The neotectonic movement has strong activity, faster strain accumulation and relatively frequent seismic action in the middle and southern sections of the fault zone, which provides a favorable regional geological environment background for the occurrence of river blocking landslide in the favorable slope areas on both sides of the Jinsha River.